Sustainable total sanitation - Nigeria: First SanMark impact evaluation report - Laura Abramovsky; Britta Augsburg; Francisco Oteiza (Institute for Fiscal Studies (IFS), 2017)
In this report, we focus on understanding the context for the Sanitation Marketing (SanMark) intervention and potential initial impacts, after its gradual development and roll-out to selected treatment areas in the Nigerian states of Ekiti and Enugu. We consider SanMark to be composed of two main phases: (i) direct work with targeted businesses to help them produce and sell a new sanitation product, as well as the provision of basic business skills training; (ii) village level door-to-door (D2D) marketing activities, to increase awareness among households of the new sanitation product and places where this could be sourced from, together with market level events and other marketing activities. At the time of collecting the latest round of data, the first component had been mostly developed and implemented, while the second was starting to be rolled out. We report our findings from analysing data collected as part of a supplier survey and as part of a second short follow-up survey on households, both carried out during April 2017. The intervention was piloted in the state of Igbo Eze North between September 2015 and February 2016. Since then, WaterAid staff have worked closely with two suppliers in this LGA.
Keywords: 330